A lithium (potassium) ion battery antimony bismuth nickel alloy negative electrode material and preparation method thereof

By using in-situ synthesis of graphitized carbon-coated antimony, bismuth and nickel ternary alloy nanoparticles in potassium ion batteries, the problem of volume expansion of antimony-based and bismuth-based negative electrode materials in potassium ion batteries is solved, and a higher level of Cycling stability and specific capacity.

CN115295776BActive Publication Date: 2025-02-18JILIN NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210790735.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-05
Publication Date
2025-02-18
Estimated Expiration
2042-07-05

AI Technical Summary

Technical Problem

In potassium ion batteries, antimony-based and bismuth-based negative electrode materials have huge volume expansion during the potassium-ionization/depotassium reaction, resulting in poor circulation performance and rapid decline in capacity. The carbon layer obtained by conventional preparation methods has low electronic conductivity and cannot be effectively suppressed. Volume variation.

Method used

In situ synthesized graphitized carbon-coated antimony, bismuth and nickel ternary alloy nanoparticles were prepared by freeze-drying and assisted in situ pyrolysis method, and the particle diameter was controlled to be 50-150nm, the carbon shell thickness was 5-25nm, and the nickel was Antimony and bismuth play a buffering role, adjusting the nickel content to adjust the crystallization degree of the carbon layer.

Benefits of technology

The cyclic stability and specific capacity of the negative electrode material of lithium (potassium) ion battery is significantly improved, the volume expansion problem is alleviated, and the electrochemical activity and electrical conductivity of the material is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115295776B_ABST
    Figure CN115295776B_ABST
Patent Text Reader

Abstract

The present invention discloses a lithium (potassium) ion battery antimony bismuth nickel alloy negative electrode material and a preparation method thereof, wherein the material is a graphitized carbon-coated antimony, bismuth and nickel ternary alloy nanoparticle, the particle diameter is 50-150nm, the carbon shell is a graphitized carbon with a thickness of 5-25nm, and the interior is a ternary alloy of antimony, bismuth and nickel; the molar ratio of antimony, bismuth and nickel is antimony: bismuth: nickel = (35-50): (35-50): (0-30). The present invention uses a freeze-drying assisted in-situ pyrolysis method to prepare graphitized carbon-coated antimony, bismuth and nickel ternary alloy nanoparticles, and the size and morphology of the particle size can be effectively controlled. The nickel generated in situ during the reaction can promote the graphitization degree of carbon, and the degree of crystallization of the carbon layer of the carbon coating layer can be adjusted by adjusting the nickel content, thereby regulating the electrochemical activity of the material. Graphitized carbon coating and inactive nickel can greatly improve the cycle stability and specific capacity of the composite material, and alleviate the huge volume expansion of the alloy-type negative electrode during the cycle.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrochemical materials, and particularly relates to an antimony, bismuth and nickel@porous carbon alloy nanoparticle active material coated with in-situ synthesized graphitized carbon, and its application in lithium ion batteries and potassium ion batteries. Background Art

[0002] The excessive exploitation and use of fossil energy have brought us serious energy crisis and environmental pollution problems, while the uneven distribution of clean energy has urgently required the development of efficient energy storage technology. Lithium-ion batteries have become one of the most efficient energy storage systems due to their high energy density and long cycle life. However, the increasing scarcity of lithium resources and high production costs have become a growing concern in the energy industry. Potassium-ion batteries, as a promising alternative to lithium-ion batteries in large-scale energy storage applications, have attracted widespread attention due to the abundance of potassium resources and similar reaction mechanisms and close redox potentials to lithium-ion batteries. The large ionic radius of potassium ions causes slow kinetics and huge volume changes during potassiumization / depotassiumization reactions, resulting in poor cycle performance and rapid capacity decline. Therefore, finding suitable electrode materials has always been a huge challenge in the development of high-performance potassium-ion batteries, especially negative electrode materials that have not only high capacity but also stable and fast charge and discharge performance. In order to alleviate the above-mentioned volume change problem, people have made great efforts in nanostructure design and electrolyte development. High-performance negative electrode materials for potassium-ion batteries include carbon materials, alloy materials, conversion negative electrodes, and organic materials. As the most studied negative electrode material in potassium ion batteries, carbon materials show excellent cycle stability but limited potassium storage capacity. Metallic antimony (Sb) can accept three potassium ions and show a storage capacity of 660 mAh g -1 The high theoretical capacity of bismuth-based materials is regarded as one of the most promising negative electrode materials. However, the huge volume expansion during the potassium alloying reaction has become a major obstacle to the application of antimony-based negative electrode materials in potassium ion batteries. Bismuth-based materials also have high theoretical capacity (384 mAh g -1 ) But it also faces a huge volume expansion problem. At the same time, the serious agglomeration of bismuth nanoparticles will cause the active material to fall off the copper foil and the material to pulverize, resulting in capacity decay and shortened life. Different metals / non-metals (such as P, Si, Sb, Sn and Bi) and their alloys have also been recently studied as electrode materials for potassium ion batteries. Their advantages include higher capacity, suitable working potential and abundant crustal content. Alleviating the volume expansion problem by adding other active or inactive metals is an effective strategy to improve the performance of antimony-based and bismuth-based electrodes. On the other hand, the carbon layer obtained by conventional preparation methods is mostly amorphous carbon with low electronic conductivity and limited inhibitory effect on the volume change of the material. Coating a highly graphitized carbon layer on the surface of the alloy negative electrode is extremely challenging and still faces difficulties. Summary of the invention

[0003] In order to solve the above problems, the present invention discloses an antimony bismuth nickel alloy negative electrode material for a lithium (potassium) ion battery and a preparation method thereof. The material is a ternary alloy nanoparticle of antimony, bismuth and nickel coated with graphitized carbon, the particle diameter is 50-150nm, the carbon shell is graphitized carbon with a thickness of 5-25nm, and the interior is a ternary alloy of antimony, bismuth and nickel; the molar ratio of antimony, bismuth and nickel is antimony:bismuth:nickel=(35-50):(35-50):(0-30).

[0004] A method for preparing an antimony-bismuth-nickel alloy negative electrode material for a lithium (potassium) ion battery is as follows:

[0005] 1) mixing a bismuth source, an antimony source and a nickel source with a pore former and a carbon source to obtain a clarified solution;

[0006] 2) freeze-drying the obtained clear solution to obtain a powder;

[0007] 3) heating the powder to 600-900°C at 1-2°C / min and calcining for 3-6 hours under vacuum or argon atmosphere protection, cooling rapidly to room temperature after calcination, and collecting the product;

[0008] 4) The product is washed, centrifuged, dried, and then powder is collected to obtain a ternary alloy of antimony, bismuth, and nickel @ carbon.

[0009] The bismuth source, antimony source and nickel source described in step 1) are metal salts, at least one of the metal salts is a metal organic acid salt, and the molar ratio of antimony, bismuth and nickel is antimony: bismuth: nickel = (35-50): (35-50): (0-30); the pore-forming agent is a soluble salt, preferably sodium chloride or potassium chloride; the carbon source is one or more of sodium dodecylbenzene sulfonate, polyvinyl pyrrolidone, polyacrylonitrile, sugars (glucose, sucrose, etc.), phenolic resin and tannic acid.

[0010] The molar ratio of the antimony salt to the bismuth salt is preferably 1:1; the antimony salt is one or more of potassium antimony tartrate, sodium antimony gluconate, antimony trichloride, and antimony sulfate. The bismuth salt is one or more of potassium bismuth citrate, bismuth nitrate, bismuth acetate, and bismuth chloride; the nickel salt is one or more of nickel citrate, nickel chloride, and nickel sulfate.

[0011] Beneficial effects of the present invention:

[0012] Bi and Sb have similar physical and chemical properties and can form solid solutions at any molar ratio (Bi x Sb 1-x). Antimony and bismuth expand greatly during the charge and discharge process, while nickel itself does not participate in the electrochemical reaction and can play a buffering role between antimony and bismuth. Both antimony and bismuth materials have excellent electrochemical properties, which can guarantee the theoretical capacity of the alloy; the nickel generated in situ during the reaction can increase the graphitization degree of carbon, and the degree of crystallization of the carbon coating layer can be adjusted by adjusting the nickel content; the reactant metal organic acid salt can not only provide active / inactive metal components, but the carbon layer generated by the in-situ carbonization of the organic ligand can perfectly coat the metal particles.

[0013] The preparation method of the graphitized carbon-coated antimony, bismuth and nickel ternary alloy nanoparticles prepared by the present invention is simple, and the process is simple and easy to operate. The size and morphology of the graphitized carbon-coated antimony, bismuth and nickel ternary alloy nanoparticles prepared by freeze-drying assisted in-situ pyrolysis can be effectively controlled. The nickel generated in situ during the reaction can promote the degree of graphitization of carbon. By adjusting the nickel content, the degree of crystallization of the carbon layer of the carbon coating layer can be adjusted, thereby regulating the electrochemical activity of the material. Graphitized carbon coating and inactive nickel can greatly improve the cycle stability and specific capacity of the composite material, and alleviate the huge volume expansion of the alloy-type negative electrode during the cycle. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is a low-resolution transmission electron micrograph of the antimony, bismuth and nickel ternary alloy@carbon nanoparticle composite material.

[0015] Figure 2 This is a high-resolution transmission electron micrograph of an antimony, bismuth and nickel ternary alloy@carbon nanoparticle composite.

[0016] Figure 3 This is the X-ray diffraction spectrum of the antimony, bismuth and nickel ternary alloy@carbon nanoparticle composite material.

[0017] Figure 4 This is a transmission electron micrograph of the graphitized carbon layer in the antimony, bismuth and nickel ternary alloy@carbon nanoparticle composite material.

[0018] Figure 5 Raman spectra of antimony, bismuth and nickel ternary alloy@carbon nanoparticle composites and I D / I G Value and G peak position as a function of nickel content.

[0019] Figure 6 The cycling stability performance diagram of lithium-ion batteries with four different proportions of antimony, bismuth and nickel ternary alloy@carbon nanoparticle composites in polyvinylidene fluoride (PVDF) binder.

[0020] Figure 7 Sb 0.4 Bi 0.4 Ni0.2 @C composite material cycling stability performance diagram of potassium ion battery under cellulose binder (CMC). DETAILED DESCRIPTION

[0021] The technical solution of the present invention is further explained and illustrated below in conjunction with the embodiments and drawings.

[0022] Example 1 (Sample A Sb 0.5 Bi 0.5 @C)

[0023] Weigh 11.7g of sodium chloride and 0.25g of polyvinyl pyrrolidone (PVP) and dissolve them in 100mL of distilled water. After stirring until the solution is clear, add 1g of potassium antimony tartrate hydrate and 2.1g of potassium bismuth citrate hydrate and stir for 12h. Transfer the obtained mixture to a freeze dryer and dry it for 24h. Place the obtained sample in a tubular furnace, heat it to 600℃ at a heating rate of 2℃ / min under an argon atmosphere for 5 hours, and filter the obtained product with distilled water and anhydrous ethanol, and collect the carbon-coated Sb after vacuum drying overnight. 0.5 Bi 0.5 @CNanoparticles.

[0024] Example 2 (Sample B Sb 0.45 Bi 0.45 Ni 0.1 @C)

[0025] Weigh 11.7g of sodium chloride and 0.25g of polyvinyl pyrrolidone (PVP) and dissolve them in 100mL of distilled water. After stirring until the solution is clear, add 0.6g of potassium antimony tartrate hydrate, 1.27g of potassium bismuth citrate hydrate and 0.072g of nickel citrate hydrate and stir for 12h. Transfer the obtained mixture to a freeze dryer and dry it for 24h. Place the obtained sample in a tubular furnace, heat it to 600℃ at a heating rate of 2℃ / min under an argon atmosphere and keep it warm for 5 hours. The obtained product is filtered with distilled water and anhydrous ethanol, and the carbon-coated Sb is collected after vacuum drying overnight. 0.45 Bi 0.45 Ni 0.1 @CNanoparticles.

[0026] Example 3 (Sample C Sb 0.425 Bi 0.425 Ni 0.15 @C)

[0027] Weigh 11.7g of sodium chloride and 0.25g of polyvinyl pyrrolidone (PVP) and dissolve them in 100mL of distilled water. After stirring until the solution is clear, add 0.57g of potassium antimony tartrate hydrate, 1.2g of potassium bismuth citrate hydrate and 0.11g of nickel citrate hydrate and stir for 12h. Transfer the obtained mixture to a freeze dryer and dry it for 24h. Place the obtained sample in a tubular furnace, heat it to 600℃ at a heating rate of 2℃ / min under an argon atmosphere for 5 hours, and filter the obtained product with distilled water and anhydrous ethanol. After vacuum drying overnight, collect the carbon-coated Sb 0.425 Bi 0.425 Ni 0.15 @CNanoparticles.

[0028] Example 4 (Sample D Sb 0.4 Bi 0.4 Ni 0.2 @C)

[0029] Weigh 11.7g of sodium chloride and 0.25g of polyvinyl pyrrolidone (PVP) and dissolve them in 100mL of distilled water. After stirring until the solution is clear, add 0.534g of potassium antimony tartrate hydrate, 1.13g of potassium bismuth citrate hydrate and 0.15g of nickel citrate hydrate and stir for 12h. Transfer the obtained mixture to a freeze dryer and dry it for 24h. Place the obtained sample in a tubular furnace, heat it to 600℃ at a heating rate of 2℃ / min under an argon atmosphere for 5 hours, and filter the obtained product with distilled water and anhydrous ethanol. After vacuum drying overnight, collect the carbon-coated Sb 0.4 Bi 0.4 Ni 0.2 @CNanoparticles.

[0030] Figure 1 and Figure 2 Sb 0.4 Bi 0.4 Ni 0.2 @C Low-resolution and high-resolution transmission electron microscopy images of nanoparticles. As shown in the images, the Sb 0.4 Bi 0.4 Ni 0.2 @C composites exhibit a carbon-coated egg yolk core-shell structure. The diameter of the monodispersed alloy particles is about 50-150nm. The structure is composed of Sb 0.4 Bi 0.4 Ni 0.2 @C nanospheres and carbon shells, the thickness of the carbon shell is about 5-25nm. Figure 3 The XRD spectra of samples B, C, and D, three different proportions of antimony, bismuth, and nickel ternary alloy @ carbon nanoparticles, show that as the percentage of nickel increases, the broad peak at 31.5° becomes more and more obvious, corresponding to the 101 plane of the NiSb crystal structure. Figure 4 In order to reveal the graphitized carbon layer formed on the surface of the antimony, bismuth and nickel ternary alloy, we used transmission electron microscopy to reveal its microstructure. In addition, as the nickel percentage in the antimony, bismuth and nickel ternary alloy increases, the carbon layer is improved, which means the enhancement of graphitization. In order to observe the changes of the graphitized carbon layer more clearly, the graphitized carbon layer is formed on the surface of the antimony, bismuth and nickel ternary alloy. Figure 5 Raman data confirmed that the increase in nickel content improves the catalytic graphitization ability of in-situ generated nickel nanoparticles.

[0031] In the above embodiments, metal organic acid salts such as potassium bismuth citrate, potassium antimony tartrate and nickel citrate are prepared in proportion, and the obtained precursor is in situ synthesized by simple pyrolysis to form graphitized carbon-coated antimony, bismuth and nickel ternary alloy nanoparticle active materials. The degree of graphitization of the carbon layer is enhanced by adjusting the content of the nickel component. Due to the high conductivity and better permeability of graphitized carbon to ions, the graphitized carbon-coated antimony, bismuth and nickel ternary alloy @ carbon negative electrode material has better cycle performance, capacity and coulomb efficiency. At the same time, the inert component nickel and the carbon-coated core-shell structure enhance the material's "resistance" to volume changes.

[0032] Performance Testing:

[0033] 1) Study on electrochemical performance of lithium-ion half-cells

[0034] In order to study the lithium storage performance of antimony, bismuth and nickel@porous carbon alloy nanoparticles anode prepared in different proportions, they were mixed with acetylene black and polyvinylidene fluoride (PVDF) at a ratio of 8:1:1 and coated on copper foil. When preparing half-cells, metallic lithium was used as the reference electrode. The anode was assembled into a 2025 type button cell using 1M lithium hexafluorophosphate (LiPF6) with 5% fluoroethylene carbonate (FEC) dissolved in a mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1 as the electrolyte. The assembly process of the half-cell was carried out in a glove box.

[0035] Test Example 1

[0036] Sample A was mixed with acetylene black and polyvinylidene fluoride (PVDF) in a ratio of 8:1:1 and coated on copper foil. When preparing the half-cell, metallic lithium was used as the reference electrode. The negative electrode was assembled into a 2025 type button cell using 1M lithium hexafluorophosphate (LiPF6) dissolved in a mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1 as the electrolyte. A: Sb 0.5 Bi 0.5 @C.

[0037] Test Example 2

[0038] Sample B was mixed with acetylene black and polyvinylidene fluoride (PVDF) in a ratio of 8:1:1 and coated on copper foil. When preparing the half-cell, metallic lithium was used as the reference electrode. The negative electrode was assembled into a 2025 type button cell using 1M lithium hexafluorophosphate (LiPF6) dissolved in a mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1 as the electrolyte. B: Sb 0.45 Bi 0.45 Ni 0.1 @C

[0039] Test Example 3

[0040] Sample C was mixed with acetylene black and polyvinylidene fluoride (PVDF) in a ratio of 8:1:1 and coated on copper foil. When preparing a half-cell, metallic lithium was used as the reference electrode.

[0041] The negative electrode was assembled into a 2025 type button cell using 1M lithium hexafluorophosphate (LiPF6) dissolved in 5% fluoroethylene carbonate (FEC) in a mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1 as the electrolyte. C: Sb 0.425 Bi 0.425 Ni 0.15 @C

[0042] Test Example 4

[0043] Sample D was mixed with acetylene black and polyvinylidene fluoride (PVDF) in a ratio of 8:1:1 and coated on copper foil. When preparing the half-cell, metallic lithium was used as the reference electrode. The negative electrode was assembled into a 2025 type button cell using 1M lithium hexafluorophosphate (LiPF6) dissolved in a mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1 as the electrolyte. D: Sb 0.4 Bi 0.4 Ni 0.2 @C

[0044] Figure 6 The cycling stability of lithium-ion half-cells assembled with the above materials is compared. In a mixture of ethylene carbonate and dimethyl carbonate with a volume ratio of 1:1, sample D (Sb 0.4 Bi 0.4 Ni 0.2 @C) The electrochemical performance is the best.

[0045] 2) Study on electrochemical performance of potassium ion half-cell

[0046] In order to study the potassium storage performance of the antimony, bismuth and nickel ternary alloy@carbon alloy nanoparticles anode with different ratios, they were mixed with acetylene black and cellulose binder (CMC) at a ratio of 8:1:1 and coated on copper foil. When preparing the half-cell, metallic potassium was used as the reference electrode. 5M potassium bis(fluorosulfonyl)imide (KFSI) dissolved in diethylene glycol dimethyl ether was used as the electrolyte, and the anode was assembled into a 2032-type button cell. The assembly process of the half-cell was carried out in a glove box.

[0047] Test Example 1

[0048] Sample A was mixed with acetylene black and cellulose binder (CMC) in a ratio of 8:1:1 and coated on copper foil. When preparing the half-cell, metallic potassium was used as the reference electrode. 5M potassium bis(fluorosulfonyl)imide (KFSI) dissolved in diethylene glycol dimethyl ether was used as the electrolyte, and the negative electrode was assembled into a 2032-type button cell. A: Sb 0.5 Bi 0.5 @C.

[0049] Test Example 2

[0050] Sample B was mixed with acetylene black and cellulose binder (CMC) in a ratio of 8:1:1 and coated on copper foil. When preparing the half-cell, metallic potassium was used as the reference electrode. 5M potassium bis(fluorosulfonyl)imide (KFSI) dissolved in diethylene glycol dimethyl ether was used as the electrolyte, and the negative electrode was assembled into a 2032-type button cell. B: Sb 0.45 Bi 0.45 Ni 0.1 @C.

[0051] Test Example 3

[0052] Sample C was mixed with acetylene black and cellulose binder (CMC) in a ratio of 8:1:1 and coated on copper foil. When preparing the half-cell, metallic potassium was used as the reference electrode. 5M potassium bis(fluorosulfonyl)imide (KFSI) dissolved in diethylene glycol dimethyl ether was used as the electrolyte, and the negative electrode was assembled into a 2032-type button cell. C: Sb 0.425 Bi 0.425 Ni 0.15 @C.

[0053] Test Example 4

[0054] Sample D was mixed with acetylene black and cellulose binder (CMC) in a ratio of 8:1:1 and coated on copper foil. When preparing the half-cell, metallic potassium was used as the reference electrode. 5M potassium bis(fluorosulfonyl)imide (KFSI) dissolved in diethylene glycol dimethyl ether was used as the electrolyte, and the negative electrode was assembled into a 2032-type button cell. D: Sb 0.4 Bi 0.4 Ni 0.2 @C.

[0055] Figure 7 The cycling stability performance diagram of the potassium ion half-cell assembled with the above materials is shown in Figure 2. In the electrolyte of 5M potassium bis(fluorosulfonyl)imide (KFSI) dissolved in diethylene glycol dimethyl ether, sample D (Sb 0.4 Bi 0.4 Ni 0.2 @C) After 600 cycles, the discharge capacity can still maintain 256.5 mAh g -1 , the capacity retention rate is about 90%. It is proved that Sb 0.4 Bi 0.4 Ni 0.2 @C has good electrochemical stability in potassium ion batteries.

Claims

1. A method for preparing an antimony-bismuth-nickel alloy negative electrode material for a lithium or potassium ion battery, characterized in that: The steps of this method are as follows: Weigh 11.7 g of sodium chloride and 0.25 g of polyvinyl pyrrolidone and dissolve them in 100 mL of distilled water; After stirring until the solution is clear, add 0.534 g of potassium antimony tartrate hydrate, 1.13 g of potassium bismuth citrate hydrate and 0.15 g of nickel citrate hydrate and stir for 12 h; The resulting mixture was transferred to a freeze dryer and dried for 24 h; The obtained sample was placed in a tube furnace and heated to 600 °C at a heating rate of 2 °C / min under an argon atmosphere for 5 hours. The obtained product was filtered with distilled water and anhydrous ethanol, and then vacuum dried overnight to collect the carbon-coated Sb 0.4 Bi 0.4 Ni 0.2 @C nanoparticles, namely the antimony bismuth nickel alloy negative electrode material of the lithium or potassium ion battery.